1997
DOI: 10.1002/j.2161-1920.1997.tb00462.x
|View full text |Cite
|
Sign up to set email alerts
|

Later Life Career Planning: A New Challenge for Career Counselors

Abstract: This article discusses the issue of later-life career planning for adults. Many older adults choose to return to employment rather than enter the traditional retirement stage of their life cycle. The article considers career options for the older adult.The twenty-first century brings a myriad of challenges for career counselors. One developing trend is the reemergence of the older adult into the workplace. As the pool for potential employees lessens and older adults are faced with increased longevity, strained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

1998
1998
2005
2005

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 7 publications
1
16
0
Order By: Relevance
“…As it relates to employment counseling of the older adult, Canaff (1997) London (1990), indicating the disastrous effects these stereotypes and biases have on the older worker community, wrote that "Moreover, such age stereotypes are probable causes of employment discrimination and lower advancement potential for older workers, thereby providing a realistic basis for declining selfconfidence" (p. 61). Brewington and Nassar-McMillan (2000) indicated further that employment counselors "should encourage workers to test their biases about themselves as well as about others.…”
Section: Employment Counseling Ofthe Older Workermentioning
confidence: 97%
See 2 more Smart Citations
“…As it relates to employment counseling of the older adult, Canaff (1997) London (1990), indicating the disastrous effects these stereotypes and biases have on the older worker community, wrote that "Moreover, such age stereotypes are probable causes of employment discrimination and lower advancement potential for older workers, thereby providing a realistic basis for declining selfconfidence" (p. 61). Brewington and Nassar-McMillan (2000) indicated further that employment counselors "should encourage workers to test their biases about themselves as well as about others.…”
Section: Employment Counseling Ofthe Older Workermentioning
confidence: 97%
“…Counselors may model assertive behaviors in presenting facts and confronting stereotypes" (p. 12). Such modeling may involve the counselor educating the client about discrimination and educating businesses about the benefits of hiring older workers (Brewington & NassarMcMillan, 2000;Canaff. 1997).…”
Section: Employment Counseling Ofthe Older Workermentioning
confidence: 98%
See 1 more Smart Citation
“…Stems and Miklos (1995) discussed the important role human resource agencies can have in fostering older workers' career growth by offering training and opportunities for challenging assignments. Canaff (1997) suggested that employment counselors can act as advocates for older workers, helping to eliminate prejudices about them and helping to educate organizations about the benefits of employing them.…”
Section: Opportunity Structures Career Development Within the Life Comentioning
confidence: 98%
“…Although the notion of opportunity structures has been implied in research on older workers' career development, it has not received thorough theoretical attention as it could be applied to this group. As noted, a body of research has documented elements that might constitute portions of the opportunity structure for older workers, for instance, the structure and requirements of contemporary organizations (Greller & Stroh, 1995), human resource agencies (Sterns & Miklos, 1995), employment counselors (Canaff, 1997), the financial and health situation of the employee (Hansson et al, 1997), and family needs (Henretta et al, 1992; Talaga & Beehr, 1995). However, these elements have not yet been accounted for using the broader framework of opportunity structures, nor have the long-term consequences of opportunity structures been explored in much detail for workers in the later career stages.…”
Section: Opportunity Structures Career Development Within the Life Comentioning
confidence: 99%